The Function of Legal Theory in the Establishment of Regional Regulation of Sustainable Spatial Based on Local Wisdom - Made Wiryani; Ni Made Jaya Senastri (Warmadewa Press, 2022)
This study aims to analyze the function of legal theory in the regional regulation establishment. Applying a normative legal research method, a conceptual approach to reveal the problem of how the function of legal theory and sustainability principle and also local wisdom in the establishment of regional regulations on spatial planning. The collected legal materials were analyzed by means of the Theory of Legislation, namely the regulation has a legal, sociological, and philosophical basis of validity; The theory of the legal system, namely the characteristics of the law of validity, efficacy, and acceptance and the theory of ecological sustainability which bring together the development and the environment through principles which are contained in adaptive policies. The results of this study show that the function of legal theory in the establishment of a regional regulation is as a basis for formulating substance to comply with legal principles and the function of the principle of sustainability and local wisdom in spatial planning is to ensure protection of the use of space for human life in the present and in the future.